Investigation on an improved heat pump AC system with the view of return air utilization and anti-fogging for electric vehicles. (25th March 2017) - Zhang, Guiying; Zou, Huiming; Qin, Fei; Xue, Qingfeng; Tian, Changqing
Highlights: An improved EV AC system using return air with continuous anti-fogging was presented. Thermal model of electric vehicle on maximum return-air-using was established. Energy-saving potential of air source heat pump & auxiliary PTC was predicted. Abstract: Utilizing the return air and fresh air properly is a promising approach to meet the demand for anti-foggy and energy-saving at the same time in electric vehicle (EV). In this paper, a concept of applying a continuous anti-fogging air curtain for front windshield glass to realize the maximum-return-air utilization in winter is presented. Accordingly, heating demand model of EV is built up by taking account of the return air ratio (RAR). The research results indicate that the heating demand can be reduced by 46.4–62.1% compared to the all-fresh-air condition when the ambient temperature is −5 °C to −20 °C. And, air source heat pump (ASHP) system performance under different RARs is tested experimentally in −20 °C ambient temperature to predict the energy-saving potentials. The coefficient of performance (COP) of ASHP decreases with the increasing of RARs. Heating capacity of ASHP presents little difference at different RARs. Equivalent COP (ECOP) is used to evaluate the EV heating, ventilation and air conditioning (HVAC) system comprehensive performance. The highest ECOP is 1.57 when the RAR is 0.46, which is 12.1% higher than that of all-fresh-air condition. Accordingly, the maximum energy saving is 40.6%. Moreover, COP change rate of ASHP with compressor speed is used to get optimal compressor speed.